Evaluasi Sistem Lalu Lintas Satu Arah pada Ruas Jalan Srijaya Negara - Nisumanti, Sartika; Putri, Yuliantini Eka; Desromi, Ferry; Qubro4, Khodijah Al; Fitri, Nofriandi; Asmara, A; Almufathir, RP (Jurnal Talenta Sipil, 2025)
The growth in the number of vehicles in the city of Palembang is not proportional to the available road capacity, leading to traffic congestion, especially in educational areas and activity centers such as the Srijaya Negara-Padang Selasa road segment. The Palembang city government has implemented a one-way system as one of its solutions to alleviate the congestion. This study aims to analyze traffic conditions before and after the implementation of a one-way system and to evaluate the effectiveness of the policy. The research was conducted on the Srijaya Negara-Padang Selasa road segment overal seven days using a traffic survey approach, vehicle volume analysis, side friction analysis, road capacity, and degree of saturation based on the Indonesian Road Capacity Guildelines (PKJI) 2023. The rusults show that the highest traffic volume occurs during peak hours, especially in segments close to the campus area. The highest side friction was recorder in segment III at 230 SF/hour. The average degree of saturation (DS) is less than 0,47, with the level of service in classes B and C, indicating that the traffic flow is relatively stable despite the speed restrictions. The implementation of a one-way system has proven capable of improving traffic flow and accesibility. As many as 80% of respondents support this policy because it has a positive impact on mobility and increases the turnover of business operators. Thus, the one-way system is worthy of continued implementation wit improvement in controlling side obstacles and enforcing traffic regulations.